Comparing morphological traits of legs of understory birds inhabiting forest areas with closed canopies and forest gaps - Supalak Siri; Yuwadee Ponpituk; Mongkol Safoowong; Wimonmart Nuipakdee; Dokrak Marod; Prateep Duengkae (Society for Indonesian Biodiversity, 2020)
Abstract. Siri S, Ponpituk Y, Safoowong M, Nuipakdee W, Marod D, Duangkae P. 2020. Comparing morphological traits of legs of understory birds inhabiting forest areas with closed canopies and forest gaps. Biodiversitas 21: 1041-1048. Bird species exhibit different adaptations depending on their habitats. The morphological traits of each species represent adaptations that are impacted by environmental changes. We conducted a 3-year study from 2015 to 2017 to compare the leg morphology of understory birds that occur under closed canopies and in forest gaps in a hill evergreen forest in northern Thailand, with gaps in the natural forest representing forest disturbances. We captured 64 bird species over the study period and measured 11 leg morphological features for each individual. Ground-foraging birds were generally long-legged and climbing birds generally short-legged. Understory species living in dense forest areas were significantly associated with long claws, toes, and tibiae, whereas species occurring in gaps and open areas tended to have shorter leg structures. Results from classification tree analysis revealed that digit claw length is the most important trait for predicting which habitat a species is most likely to occupy. Our findings suggest that understory birds with long leg structures that live under closed canopies are most vulnerable to forest disturbances or the conversion of forests to large-scale open areas.